PEMBUATAN PERLENGKAPAN PENGAMAN JALAN UNTUK MENINGKATKAN AKSESIBILITAS JALAN WISATA PANTAI BLIMBINGSARI - Rodiyani, Megalita; Ulfiyati, Yuni; Hardiyanti, Siska Aprilia (LPPM Universitas Bina Bangsa, 2025)
Insufficient road security around the Blimbingsari Beach tourist attraction causes low accessibility for visitors. This condition is a problem that needs to be resolved so that visitors to the Blimbingsari Beach tourist attraction have comfort while travelling. The dedication is aimed at solved this problem with a system approach in handling road safety. Through analysis of the factors that influence road safety and accessibility, as well as identifying the impact of a lack location of road security on accidents and limited acces. Road safety solutions that are appropriate to site conditions and needs, including the installation of warning signs, traffic signs and through and safe road infrastructure, design and implemented through a participatory process involving local communities and related stakeholders. This service activity improve road safety and accessibility to Blimbingsari Beach, minimize accidents, and provide a better experience for tourist visitors.